Running-specific prostheses limit ground-force during sprinting - Grabowski, A. M.; McGowan, C. P.; McDermott, W. J.; Beale, M. T.; Kram, R.; Herr, H. M. (Biology letters, 2010)
Running-specific prostheses (RSP) emulate the spring-like behaviour of biological limbs during human running, but little research has examined the mechanical means by which amputees achieve top speeds. To better understand the biomechanical effects of RSP during sprinting, we measured ground reaction forces (GRF) and stride kinematics of elite unilateral trans-tibial amputee sprinters across a range of speeds including top speed. Unilateral amputees are ideal subjects because each amputee's affected leg (AL) can be compared with their unaffected leg (UL). We found that stance average vertical GRF were approximately 9 per cent less for the AL compared with the UL across a range of speeds including top speed (p < 0.0001). In contrast, leg swing times were not significantly different between legs at any speed (p = 0.32). Additionally, AL and UL leg swing times were similar to those reported for non-amputee sprinters. We infer that RSP impair force generation and thus probably limit top speed. Some elite unilateral trans-tibial amputee sprinters appear to have learned or trained to compensate for AL force impairment by swinging both legs rapidly.